Rancang Bangun Low-Budget Autonomous Quadcopter - Budi Hartono (Department of Mechanical Engineering, Universitas Andalas, 2021)
Quadcopter is an unstable flying vehicle. The flight controller regulates the rotational speed of the four motors, so that each propeller produces the lift required for the quadcopter to fly stable. It is interesting to know whether the use of generic quadcopter components obtained in the market can be mutually compatible. A stable and controllable quadcopter is a requirement for a quadcopter to fly autonomously. This research focusses on design a low-budget autonomous quadcopter. The research method consists of three main stages. First, the design and build phase of the quadcopter. The main frame and quadcopter arms are designed with a diagonal distance between the rotors of 45 cm. The basic components of the quadcopter are selected which are mutually compatible and assembled on the frame and arms. The flight controller is connected to the GPS, transmitter, and receiver. The autonomous system also involves a ground control system in the form of a Mission Planner. Second, the flight test stage is setting the PID constant so that the quadcopter can fly stable. PID tuning produces proportional constants of 0.088, integrals of 0.016, and derivatives of 0.008. Third, the autonomous flight test stage. The success of autonomous flying is known by analyzing the difference in input waypoint coordinates through the Mission Planner against the results of low-budget GPS receiver readings on autonomous flying missions. GPS accuracy was analyzed by calculating the 2DRMS and CEP values. The best value of 2DRMS = 1.56 meters and CEP = 0.64 meter occurred at Waypoint #2.